DJ-1 regulates mitochondrial function and promotes retinal ganglion cell survival under high glucose-induced oxidative stress - Peng, Hanhan; Li, Haoyu; Ma, Benteng; Sun, Xinyue; Chen, Baihua (Frontiers in Pharmacology, 2024)
Purpose: This study aimed to investigate the antioxidative and neuroprotective effects of DJ-1 in mitigating retinal ganglion cell (RGC) damage induced by high glucose (HG). Methods: A diabetic mouse model and an HG-induced R28 cell model were employed for loss- and gain-of-function experiments. The expression levels of apoptosis and oxidative stress-related factors, including Bax, Bcl-2, caspase3, Catalase, MnSOD, GCLC, Cyto c, and GPx-1/2, were assessed in both animal and cell models using western blotting. Retinal structure and function were evaluated through HE staining, electroretinogram, and RGC counting. Mitochondrial function and apoptosis were determined using JC-1 and TUNEL staining, and reactive oxygen species (ROS) measurement. Results: In the mouse model, hyperglycemia resulted in reduced retinal DJ-1 expression, retinal structural and functional damage, disrupted redox protein profiles, and mitochondrial dysfunction. Elevated glucose levels induced mitochondrial impairment, ROS generation, abnormal protein expression, and apoptosis in R28 cells. Augmenting DJ-1 expression demonstrated a restoration of mitochondrial homeostasis and alleviated diabetes-induced morphological and functional impairments both in vivo and in vitro. Conclusion: This study provides novel insights into the regulatory role of DJ-1 in mitochondrial dynamics, suggesting a potential avenue for enhancing RGC survival in diabetic retinopathy.